2013
DOI: 10.1016/j.mjafi.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human parvovirus B19 in healthy blood donors

Abstract: a b s t r a c tBackground: Human parvovirus B19 is an emerging transfusion transmitted infection.Although parvovirus B19 infection is connected with severe complications in some recipients, donor screening is not yet mandatory. To reduce the risk of contamination, plasma-pool screening and exclusion of highly viraemic donations are recommended. In this study the prevalence of parvovirus B19 in healthy blood donors was detected by ELISA.Methods: A total of 1633 samples were screened for IgM and IgG antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
4
11
0
1
Order By: Relevance
“…Viral load was no detected in some controls with IgG or IgM/IgG antibodies. In this regard, it has been reported that immunocompetent individuals produce antibodies that effectively eliminate viremia within a few days of infection, and the infection is often not developed, is asymptomatic or has mild clinical manifestations (like the common cold) 55 , which seems to agree with what we found in our controls. On the other hand, there have also been rare cases of chronic PV-B19 infection in healthy individuals, with involvement of the central nervous system, causing nonspecific symptoms such as fatigue, fever, arthralgia and myalgia, which may hinder the diagnostic 56 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Viral load was no detected in some controls with IgG or IgM/IgG antibodies. In this regard, it has been reported that immunocompetent individuals produce antibodies that effectively eliminate viremia within a few days of infection, and the infection is often not developed, is asymptomatic or has mild clinical manifestations (like the common cold) 55 , which seems to agree with what we found in our controls. On the other hand, there have also been rare cases of chronic PV-B19 infection in healthy individuals, with involvement of the central nervous system, causing nonspecific symptoms such as fatigue, fever, arthralgia and myalgia, which may hinder the diagnostic 56 .…”
Section: Discussionsupporting
confidence: 93%
“…La carga viral no se detectó en algunos controles con anticuerpos IgG o IgM / IgG. A este respecto, se ha reportado que los individuos inmunocompetentes producen anticuerpos que eliminan efectivamente la viremia a los pocos días de la infección, y la infección no suele desarrollarse, es asintomática o tiene manifestaciones clínicas leves (como el resfriado común) 55 , lo que parece correlacionar con lo que encontramos en nuestros controles. Por otra parte, también se han registrado casos raros de infección crónica por PV-B19 en individuos sanos, con afectación del sistema nervioso central, causando síntomas inespecíficos como fatiga, fiebre, artralgia y mialgia, lo que puede dificultar el diagnóstico 56 .…”
Section: Discussionunclassified
“…We detected a seroprevalence of 62.2% and the positivity of IgM was 0.06% in SANBS blood donors which is comparable with the seroprevalence in other reports . Varying PVB19 IgG prevalence has been reported ranging from 6% to 82.3% .…”
Section: Discussionsupporting
confidence: 88%
“…B19 infection can lead to serious consequences in ‘at risk’ groups, such as organ transplant recipients, thalassaemia and sickle cell anaemia patients and foetus in utero 6 . There are no population-based seroprevalence studies from India on parvovirus B19, although studies conducted among blood donors 7 8 and hospital-based studies 9 are reported. Seroprevalence data of B19 in pregnant women are also lacking from India.…”
mentioning
confidence: 99%